(3Jbhje GdUMI HGdCSHGH GdSJIs - (3GHf HWdGf , GdeNJGQ Hf GdMSf Hf YHOhf, CHh GdMSf,J (B458 (3g` s
(3ChdgG (B:s
(3cJGH Jbhje GdUMI HGdCSHGH GdSJI GdJi dGHO dcd EfSGf jDKQ OhGe UMJg ef JYOjdgG hGSJYeGdgG hChdgG EUdGM GdghGA GdhGUd Edi bdHg , hGdKGfi JbOjQ eBcdg heTGQHg , hGdKGdK JYOjd MQcGJg hSchfg , hGdQGHY s
(3BNQgG (B:s
(3cJGHkG Ufa ajeG GfG HSHjdg EdG hbO bQGJg YfO JUfja gPG , EKGQkG efi GdJbQH Edi bdhH SGOJi hENhGfi hGddg (B[ (3fSCd Cf jdgefG (B] (3TcQg hMeOg , ceG gh Cgdg heSJMbg s
(3GfXQ agQS GdWH (B" 67 " (3Jbhje GdUMI (B"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B210s
(3agQS GdWH (B- (3U (B85 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B66 s
(3eUOQ GbJfGA GdCUd (B:s
(3cJGHNGfg eQcRi (B_ (3LGeYI WgQGf (B(1239) s
Keywords: (3GdWHs